Leemos un texto narrativo - Gutierrez Bacilio, Karen Abeli (2020)
The lesson entitled " "We read a narrative text"", designed for third grade of Primary Education, aims to develop in the child develop reading in the child, considering in him the development of the communicative approach. The present research work is on the approach communicative approach and active citizenship, with a learning session design relevant to the area, thus ensuring the achievement of the competence read various types of text. Likewise, this work is based on two aspects: first the Theoretical Support, which shows the main theoretical bases and finally the Pedagogical Support that supports all the processes applied and developed in the learning session design.